2017
DOI: 10.1089/fpd.2017.2295
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Antimicrobials and Essential Oils as an Alternative for the Control ofSalmonella entericaMultiresistant Strains Related to Foodborne Disease

Abstract: Due to the increase in bacterial resistance to antimicrobials (AMBs) commonly used in veterinary and human medicine, the new strategies for controlling zoonoses focus on the study of natural products with demonstrated AMB activity, such as essential oils (EOs). The aim of this study was to evaluate the in vitro effect of the combination of enrofloxacin (ENR), ceftiofur (CEF), and trimethoprim-sulfamethoxazole (SXT) with cinnamon, clove, oregano, and red thyme EOs against multiple drug-resistant strains of Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…However, the nontoxic concentration of cinnamon that they publish was lower than our values. Several studies have shown synergistic effect between the essential oils tested in this work and some traditional antimicrobials, with a notable decrease in the effective concentration (Solarte et al., ).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the nontoxic concentration of cinnamon that they publish was lower than our values. Several studies have shown synergistic effect between the essential oils tested in this work and some traditional antimicrobials, with a notable decrease in the effective concentration (Solarte et al., ).…”
Section: Resultsmentioning
confidence: 80%
“…However, the nontoxic concentration of cinnamon that they publish was lower than our values. Several studies have shown synergistic effect between the essential oils tested in this work and some traditional antimicrobials, with a notable decrease in the effective concentration (Solarte et al, 2017). In vivo studies in pigs with oregano, thyme, and cinnamon generally describe a significant increase in growth performance without altering the quality of the carcass (Namkung et al, 2004;Simitzis, Symeon, Charismiadou, Bizelis, & Deligeorgis, 2010), which is associated with a beneficial effect on the intestinal microbiota, nutrient absorption, and on the action of digestive enzymes (Zeng, Zhang, Wang, & Piao, 2015).…”
Section: Minimal Inhibitory Concentration and Minimal Bactericidal mentioning
confidence: 72%
“…A recent study also reported synergistic effect of Eucalyptus camaldulensis with polymyxin B against MDR Acinetobacter baumannii ( Knezevic et al, 2016 ). In another study, Enrofloxacin and cinnamon were observed to possess synergistic effect against Salmonella enterica ( Solarte et al, 2017 ). Further, extracts of medicinal plant Holarrhena antidysenterica with Conessine increased susceptibility of extensively drug resistant A. baumannii to novobiocin and rifampicin ( Siriyong et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…The combination of oxytetracycline with cinnamon resulted in synergy for 2/5 strains, and additive for 3/5 strains, this interaction has also been observed in previous studies with Salmonella enterica , an important foodborne pathogen (Bassole and Juliani ; Solarte et al . ). The combination of penicillin (Fig.…”
Section: Resultsmentioning
confidence: 97%